Perceived professionalism and its relationship with communication skills, social interaction and attitude towards medical subjects among undergraduate medical students in Malaysia - Rahman, M. Mizanur; Raman, Daneish; Anthony, Elvyronna; Hazwani, Nor Syamimi; Iffah, Nurul (International Journal of Research in Medical Sciences, 2023)
Background: Professionalism is an essential core competency in medical education in line with societal expectations. It is expected that the medical professionals show a specified set of behaviours and attitudes towards patients and society. This study assessed professionalism and its relationship with undergraduate medical students’ communication competency skills, learning attitude, and social interaction. Methods: This was a cross-sectional-correlation study conducted among undergraduate medical students irrespective of gender and nationality. A total of 319 students’ data were collected using a validated self-administered questionnaire. The collected data were analysed using IBM SPSS version 27.0. Pearson’s moment correlation and multiple linear regression analysis were done to identify the potential predictors of perceived medical professionalism. A p value of less than 0.05 was considered statistically significant. Results: The study showed that professional relationship was significantly correlated with a positive attitude on communication skill (p<0.001), environmental control (p<0.001), interaction management (p<0.01), immediacy (p<0.01), attitude towards the medical subject (p<0.001). However, no statistically significant correlation was found between perceived empathy and age, gender, year of study, parental education and previous CGPA (p>0.05). Conclusions: The study found an interrelationship between professionalism, communication skills, interpersonal communication, and attitude towards medical subjects. However, the multivariate analysis revealed different weightage of influence to professionalism. Further advanced analysis is warranted to get the impact of each of the contributing variables to academic achievement.